2015
DOI: 10.1128/aac.01447-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Functional Portrait of a Highly Virulent, CTX-M-15-Producing H 30-Rx Subclone of Escherichia coli Sequence Type 131

Abstract: Escherichia coli sequence type 131 (ST131) is a pandemic clone associated with multidrug-resistant, extraintestinal infections, attributable to the presence of the CTX-M-15 extended-spectrum ␤-lactamase gene and mutations entailing fluoroquinolone resistance. Studies on subclones within E. coli ST131 are critically required for targeting and implementation of successful control efforts. Our study comprehensively analyzed the genomic and functional attributes of the H30-Rx subclonal strains NA097 and NA114, bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…From the BLASTn ( 37 ) analysis of 139 strains against the downloaded Plasmid Finder database ( 38 ), it was observed that 98 out of 99 strains of ST131 harbored IncF plasmids. Among them, the in-house strains NA097 ( 39 ), NA101, and NA114 ( 40 ) harbored an IncF plasmid with pMLST profile F2:A1:B−, while NA112 had IncF with F4:A−:B− (see Table S3 in the supplemental material). These two pMLST profiles were earlier reported to be most common among the ST131 strains ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the BLASTn ( 37 ) analysis of 139 strains against the downloaded Plasmid Finder database ( 38 ), it was observed that 98 out of 99 strains of ST131 harbored IncF plasmids. Among them, the in-house strains NA097 ( 39 ), NA101, and NA114 ( 40 ) harbored an IncF plasmid with pMLST profile F2:A1:B−, while NA112 had IncF with F4:A−:B− (see Table S3 in the supplemental material). These two pMLST profiles were earlier reported to be most common among the ST131 strains ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve strains, comprising four from each of the three disease types, were subjected to comparative genomic analysis to obtain a broader perspective of the complexity of the E. coli disease types. Genome sequence data for four strains were also included from previous and ongoing studies, including reference strains Escherichia coli NA097 and NA114 ( 10 , 11 ), and eight isolates of this study were subjected to whole-genome sequencing (WGS). Whole-genome-based resistome profiles confirmed the strains to be multidrug resistant.…”
Section: Resultsmentioning
confidence: 99%
“…ExPEC is known to be evolving and disseminating globally via clonal expansion, with clones of similar genetic architectures but also demonstrating strain-specific features ( 11 , 18 ). Here, we observed similarities in virulence and resistance coordinates of strains belonging to sequence types (STs) ST131, ST38, ST68, ST405, and ST617.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our group have shown an endemic E. coli infection burden and the presence of clonal group ST131 isolates with NDM-1 (23)(24)(25)50). This study was aimed at detection, comprehensive characterization, and whole-genome sequence analysis of MBL-producing MDR organisms that can lead to successful infection.…”
Section: Discussionmentioning
confidence: 99%
“…(19)(20)(21)(22). Our previous studies have put forward strong evidence for the widespread occurrence of ST131 strains among extraintestinal infections in India and have also reported the existence of NDM-1-positive ST131 E. coli, thus representing a serious therapeutic challenge (23)(24)(25)(26)(27). This, together with the implication of NDM-producing strains globally, warrants serious attention of health care specialists and epidemiologists with respect to surveillance and resistance tracking in India and elsewhere so as to monitor threats locally and globally.…”
mentioning
confidence: 99%